The Role of Genome-Wide Association Study in Pulmonary Disease Diagnostics: A Review in Medical Bioinformatics - Andromeda, Rossalyn; Pratomo, Irandi Putra; Fauzi, Ahmad; Kinasih, Tutug; Prasenohadi, Prasenohadi; Santoso, Arif; Tokumo, Kentaro (Faculty of Medicine Universitas Airlangga, 2024)
Biomedical science, which initially required only conventional research in the laboratory, currently involves information technology and has created bioinformatics in its development. Bioinformatics, a branch of biology, quantitatively analyzes information within biological macromolecules using software. Contemporary applications of bioinformatics have advanced biotechnological, medical, and pharmaceutical practices. Among the established applications of bioinformatics is diagnosing lung diseases using the genome-wide association study (GWAS) technique. Owing to sequencing technology and rapid computational methods, this technique is applied to analyze the link between genes with essential traits in the population, thus mapping the target genes to diagnose and treat diseases. The lung diseases diagnosed using GWAS include the responsible locus in asthma, chronic obstructive pulmonary disease (COPD), and lung cancer. Moreover, it can identify the treatment for COPD and suggest a new locus in lung cancer. Advancing the current gene-mapping technology demands genotype and phenotype data to study disease-linked genomes. Currently, bioinformatics is barely known and receives little attention in Indonesia. However, it can grow rapidly through open-source basis data and cross-disciplinary collaboration.